2016
DOI: 10.1177/0886260516639255
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Violence and Relationship Abuse on Grades of American Indian/Alaska Native Undergraduate College Students

Abstract: Violence and relationship abuse are pervasive public health problems that have a range of negative effects, with exceptionally high prevalence among ethno-racial minority youth. This study assesses the prevalence of these types of violence among American Indian/Alaska Native (AI/AN) students and examines the impact of victimization on academic performance of AI/AN and non-AI/AN student populations using self-reported college health survey data. Results show that students who identified fully or partially as AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Several studies have shown that students who identify as gay, bisexual, or transgender experience similar or even higher rates of sexual violence victimization when compared to heterosexual female students (Coulter & Rankin, 2017; Ford & Soto-Marquez, 2016). Although a full review of differential risk is outside the scope of this review, research has identified other groups with high rates of sexual assault, such as students with disabilities (Findley, Plummer, & McMahon, 2016; Scherer, Snyder, & Fisher, 2016) and Native American students (Patterson Silver Wolf, Perkins, Zile-Tamsen, & Butler-Barnes, 2016), and other research has identified lower rates among groups such as international students (Daigle, Hoffman, & Johnson, 2016).…”
Section: Ecological Review Of Campus Sexual Violencementioning
confidence: 99%
“…Several studies have shown that students who identify as gay, bisexual, or transgender experience similar or even higher rates of sexual violence victimization when compared to heterosexual female students (Coulter & Rankin, 2017; Ford & Soto-Marquez, 2016). Although a full review of differential risk is outside the scope of this review, research has identified other groups with high rates of sexual assault, such as students with disabilities (Findley, Plummer, & McMahon, 2016; Scherer, Snyder, & Fisher, 2016) and Native American students (Patterson Silver Wolf, Perkins, Zile-Tamsen, & Butler-Barnes, 2016), and other research has identified lower rates among groups such as international students (Daigle, Hoffman, & Johnson, 2016).…”
Section: Ecological Review Of Campus Sexual Violencementioning
confidence: 99%
“…Bisexual women have also been found to be at the highest risk of SA compared to heterosexual women and gay men, followed by bisexual men, heterosexual men, and lesbian women (Ford & Soto-Marquez, 2016). Results have been mixed in regard to race and ethnicity, with some studies finding that racial/ethnic minorities may be less likely to experience SA (Gardella et al, 2015;Krebs et al, 2011) and others suggesting increased risk for some racial/ethnic minority students Patterson Silver Wolf, Perkins, Van Zile-Tamsen, & Butler-Barnes, 2016) when compared to Caucasian students. These demographic factors are also often studied as an individual-level characteristic related to victimization risks but can be conceptualized as a macro-level variable as well (Moylan & Javorka, 2018).…”
Section: Sexual Assault Among College Studentsmentioning
confidence: 99%
“…To date, only three studies to our knowledge has focused specifically on IPV among Indigenous college students (Dion et al, 2021; Patterson Silver Wolf et al, 2018; Qeadan et al, 2021). First, secondary data analysis from four waves of the American College Health Association’s National College Health Survey (NCHS) documented concerning rates of past-year IPV among Indigenous students, specifically: emotional IPV victimization: 13%–14%, physical IPV victimization: 3%–6%, and sexual IPV victimization: 1% (Patterson Silver Wolf et al, 2018).…”
mentioning
confidence: 99%
“…To date, only three studies to our knowledge has focused specifically on IPV among Indigenous college students (Dion et al, 2021; Patterson Silver Wolf et al, 2018; Qeadan et al, 2021). First, secondary data analysis from four waves of the American College Health Association’s National College Health Survey (NCHS) documented concerning rates of past-year IPV among Indigenous students, specifically: emotional IPV victimization: 13%–14%, physical IPV victimization: 3%–6%, and sexual IPV victimization: 1% (Patterson Silver Wolf et al, 2018). Further, Qeadan et al (2021) conducted a secondary analysis using a subsample of Indigenous college students who completed the American College Health Association National College Health Assessment II (NCHA) and documented that 15% of Indigenous college students reported IPV experiences in the past year and these experiences were positively related to opioid misuse (taking opioids that were not prescribed to them).…”
mentioning
confidence: 99%
See 1 more Smart Citation